Praktik Doa Umat Hindu: Studi Pada Kuil Shri Mariamman dan Pura Agung Raksa Buana di Kota Medan - Pasaribu, Wina Safitri Br; Lubis, Dahlia; Jailani, Muhammad (Kamaya: Jurnal Ilmu Agama, 2025)
This study reviews the meaning and how prayer is carried out in Hindus. In Hinduism, prayer (mantra/puja) is a form of worship carried out to pray to Sang Hyang Widhi Wasa and his manifestations of gods and goddesses and ask for blessings. Based on this background, the aim of this research is to find out knowledge about prayer in Indonesian Hindu and Tamil religions that can be applied and applied in the context of worship practices and the meaning they contain. This research is a type of qualitative field research, namely research procedures that use various methods to discover, define, understand and explain the meaning of phenomena. This research was conducted at two Hindu temples, namely Shri Mariamman Temple and Pura Agung Raksa Buana in Medan City. The results of this research show that Hinduism teaches the practice of Tri Sandhya because it has two main basics that are needed by the physical and spiritual in order to navigate the ark of life with full benefit. The analysis that the author can take is that in the practice of Tri Sandhya, basically in Hinduism to achieve happiness and gratitude to God by doing this prayer. Even though the path or method used is different in the practice of worship from other religions. However, showing gratitude to God remains the same and the author's analysis states that belief in religion is human nature, and each religion believes in the truth of its own religion. This Tri Sandhya can be a driving force for us towards salvation of the soul and shows a servant’s obedience to the Creator. Chanting or japa, in Tamil and Indonesian Hindu traditions is the practice of repeating mantras to achieve concentration and spirituality.